Perforation in duplicated intestinal segment: a rare presentation - Mahato, Anup Kumar; Ekka, Nishith M. Paul; Kar, Pritam (International Surgery Journal, 2024)
Enteric duplication is very rare congenital anomaly present mainly with the complain of abdominal pain, perforation, intestinal obstruction and sometimes GI bleeding posing a challenge in diagnosis due to nonspecific symptoms that may mimic other pathologies. Furthermore, the management options including total resection, mucosal striping, and internal drainage of the duplicate depend on the presentation of the patient, site, and length of the involved bowel. In this report we describe a case of ileal duplication in a 65 year old male patient without any prior gastrointestinal morbidity who presented with abdominal pain and distension and underwent exploratory laparotomy for suspected gastrointestinal perforation.